2004
DOI: 10.1002/jemt.20024
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural features of bone marrow cells from patients with acquired sideroblastic anemia

Abstract: The ultrastructural findings of the bone marrow cells from 15 patients with acquired sideroblastic anemia are presented. The red cell precursors from all patients showed the presence of electron-dense material in the mitochondria, representing most probably iron deposits. A great number of these mitochondria were completely destroyed. The erythropoietic precursors from one of the patients showed markedly elongated mitochondria that measured up to 3 microm. In addition numerous cytoplasmic vacuoles were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Fanconi's anemia granulocytes Barton et al 1987 Acquired sideroblastic anemia granulocytes Djaldetti et al 2004 Megaloblastic anemia (B12 deficiency) granulocytes Bunting and Selig 2002;Bunting et al 1996 Congenital dyserythropoietic anemia (CDA) erythrocyte precursors Bjorksten et al 1978 Chromosomal aneuploidy D 1 (13-15) trisomy granulocytes Fine et al 1965;Huehns et al 1964;Lutzner and Hecht 1966;Mehes 1966;Rogers 1984;Salama et al 2004 14 trisomy granulocytes Dallapiccola et al 1984 21 Trisomy (Down's Syndrome) granulocytes Djaldetti et al 1974;Gericke et al 1977 Various combinations of aneuploidy, translocations and inversions granulocytes Ahearn et al 1974;Dalton et al 1987;Tricot and Broeckaert-Van Orshoven 1984 Chemotherapy/mitotic agents 5-Fluorouracil granulocytes Stalzer et al 1965 Cytosine arabinoside granulocytes Ahearn et al 1967 Mitotic inhibitor SK & F Burkitt's lymphoma cells Erenpreisa et al 2002 Phytohemagglutinin Blood mononuclear cells Mollo and Stramignoni 1967 Sodium periodate CLL cells McGill et al 1976 Cytochalasin B and concanavalin A lymphocytes Viklicky et al 1978 B12 deficiency), which is thought to provoke a perturbation of DNA replication in the bone marrow (Bunting and Selig 2002;Bunting et al 1996). It may be that the common feature of these cell cycle insults is the induction of a "mitotic crisis" (Erenpreisa et al 2002).…”
Section: Lymphomamentioning
confidence: 99%
“…Fanconi's anemia granulocytes Barton et al 1987 Acquired sideroblastic anemia granulocytes Djaldetti et al 2004 Megaloblastic anemia (B12 deficiency) granulocytes Bunting and Selig 2002;Bunting et al 1996 Congenital dyserythropoietic anemia (CDA) erythrocyte precursors Bjorksten et al 1978 Chromosomal aneuploidy D 1 (13-15) trisomy granulocytes Fine et al 1965;Huehns et al 1964;Lutzner and Hecht 1966;Mehes 1966;Rogers 1984;Salama et al 2004 14 trisomy granulocytes Dallapiccola et al 1984 21 Trisomy (Down's Syndrome) granulocytes Djaldetti et al 1974;Gericke et al 1977 Various combinations of aneuploidy, translocations and inversions granulocytes Ahearn et al 1974;Dalton et al 1987;Tricot and Broeckaert-Van Orshoven 1984 Chemotherapy/mitotic agents 5-Fluorouracil granulocytes Stalzer et al 1965 Cytosine arabinoside granulocytes Ahearn et al 1967 Mitotic inhibitor SK & F Burkitt's lymphoma cells Erenpreisa et al 2002 Phytohemagglutinin Blood mononuclear cells Mollo and Stramignoni 1967 Sodium periodate CLL cells McGill et al 1976 Cytochalasin B and concanavalin A lymphocytes Viklicky et al 1978 B12 deficiency), which is thought to provoke a perturbation of DNA replication in the bone marrow (Bunting and Selig 2002;Bunting et al 1996). It may be that the common feature of these cell cycle insults is the induction of a "mitotic crisis" (Erenpreisa et al 2002).…”
Section: Lymphomamentioning
confidence: 99%
“…In normal skeletal muscle biopsies, absence of brown DAB-enhanced Prussian blue staining is indicative of normal levels of ferric iron (d) , whereas brown punctate deposits reveal mitochondrial iron overload throughout the individual muscle fibers of patients with myopathy and ISCU deficiency (e) , a finding that has been confirmed by electron microscopy (f) [54]. In human sideroblastic anemias, dark deposits within distorted mitochondria are caused by iron overload [64]. Electron microscopy analysis of normoblasts (normal red cell precursors) of a patient from an early stage in development of acquired sideroblastic anemia showed that most of the mitochondria were still well preserved (as evidenced by well preserved cristae) (g) , whereas in the sideroblasts at later stages, the mitochondria became distorted and increasingly loaded with iron, which appears as black deposits within the matrix (h and i) .…”
Section: Friedreich Ataxia: the Role Of Frataxin In Iron–sulfur Clustmentioning
confidence: 99%
“…String mitochondria can be induced in mouse hepatocytes by administration of the copper‐chelator, penicillamine (Walter et al, ). Slender, elongated mitochondria are present in bone marrow cells of patients with sideroblastic anemia (Djaletti et al, ). Very long mitochondria are not found exclusively in animal cells; such organelles also have been depicted in cells of the thale cress, Arabidopsis thaliana (Arimura et al, ).…”
Section: Introductionmentioning
confidence: 99%